Modeling and Analysis of a Horizontal Direct Chill Casting Process - Garðar Garðarsson 1984- (2012)
The objective of this study is to investigate bleedouts in Horizontal Direct Chill casting process and to make a complete finite volume model of such process. The casting machine that was investigated and used as a reference for the numerical model, was the HDC casting machine at Alcoa Fjarðaál in Iceland. One of Fjarðaál‘s main production problems are bleedouts in the HDC casting machine and the consequences of recurrent bleedouts is production loss. To analyse the problem, historical data were examined and measurements were performed in the process. The numerical model was used to support the research. To simulate the current state, measurements were used to construct the numerical model. It was focused on examining the main control parameters in the casting process and their impact on the probability of bleedouts. The goal was to identify which control parameter is most critical and realise how it is possible to reduce number of bleedouts or prevent it. The study showed that the temperature of the aluminium alloy is the most sensitive control parameter. Furnace exchange has also a influence on bleedouts, it includes discrepancy between furnaces. Markmið þessarar rannsóknar var að rannsaka blæðingar í láréttu sísteypuferli (HDC) sem framleiðir melmisstangir úr áli og að búa til nákvæmt reiknilíkan af slíku ferli. Steypuvélin sem var rannsökuð og notuð sem viðmið fyrir líkansmíðina, var lárétt steypuvél Alcoa Fjarðaáls á Íslandi. Eitt helsta framleiðsluvandamál Fjarðaáls eru blæðingar í láréttu steypuvélinni og afleiðingar síendurtekinna blæðinga er framleiðslutap. Til að greina vandamálið voru söguleg gögn skoðuð og mælingar framkvæmdar í ferlinu. Reiknilíkanið var notað til að styðja við rannsóknina. Til að ná að herma núverandi ástand voru mælingar notaðar til að byggju upp reiknilíkanið. Lögð var áherslu á að skoða helstu stýribreytur í steypuferlinu og áhrif þeirra á líkindi blæðinga. Takmarkið var að finna hvaða stýribreyta væri mikilvægust fyrir ferlið og átta sig á því hvernig mögulega væri hægt að ...